Grading and Risk-Adjusted Performance of Indian IPOs - Singh, Harendra; Sastry, C. G. (Indian Journal of Finance, 2014)
Most studies on price performance of Indian IPOs have strengthened international evidence that there would be a strong underpricing in the short run, but negative returns in the long-run. To solve the problem of mispricing and include more transparency, SEBI mandated the grading of IPOs by recognized credit rating agencies from May 1, 2007. The mandatory grading process is expected to give an independent assessment of the fundamentals of the issue. In this research paper, we tried to ascertain the impact of grading on the performance of IPO firms. We attempted to understand the efficacy of the grading mechanism in place to address the problems associated with adverse selection and improve pricing efficiency.